Community participation in the health system: analyzing the implementation of community health committee policies in Kenya. (28th April 2023) - Karuga, Robinson; Dieleman, Marjolein; Mbindyo, Patrick; Ozano, Kim; Wairiuko, Judy; Broerse, Jacqueline E.W.; Kok, Maryse
Abstract: Background: Community health committees (CHCs) are a mechanism for communities to voluntarily participate in making decisions and providing oversight of the delivery of community health services. For CHCs to succeed, governments need to implement policies that promote community participation. Our research aimed to analyze factors influencing the implementation of CHC-related policies in Kenya. Methods: Using a qualitative study design, we extracted data from policy documents and conducted 12 key informant interviews with health workers and health managers in two counties (rural and urban) and the national Ministry of Health. We applied content analysis for both the policy documents and interview transcripts and summarized the factors that influenced the implementation of CHC-related policies. Findings: Since the inception of the community health strategy, the roles of CHCs in community participation have been consistently vague. Primary health workers found the policy content related to CHCs challenging to translate into practice. They also had an inadequate understanding of the roles of CHCs, partly because policy content was not adequately disseminated at the primary healthcare level. It emerged that actors involved in organizing and providing community health services did not perceive CHCs as valuable mechanisms for community participation. County governments did not allocate funds to support CHC activities, and policies focused more on incentivizing community health volunteers (CHVs) who, unlike CHCs, provide health services at the household level. CHVs are incorporated in CHCs. Conclusion: Kenya's community health policy inadvertently created role conflict and competition for resources and recognition between community health workers involved in service delivery and those involved in overseeing community health services. Community health policies and related bills need to clearly define the roles of CHCs. County governments can promote the implementation of CHC policies by including CHCs in the agenda during the annual review of performance in the health sector.